Clinical course and short‐term mortality of cirrhotic patients with infections other than spontaneous bacterial peritonitis. (20th September 2016) - Fernández, Javier; Acevedo, Juan; Prado, Verónica; Mercado, Mario; Castro, Miriam; Pavesi, Marco; Arteaga, Mireya; Sastre, Lydia; Juanola, Adria; Ginès, Pere; Arroyo, Vicente
Abstract: Background & Aims: Clinical course and risk factors of death in non‐spontaneous bacterial peritonitis (SBP) infections are poorly known. We assessed the prevalence of acute kidney injury (AKI) and type‐1 hepatorenal syndrome (HRS), hospital, 30‐day and 90‐day mortality and risk factors of death in 441 decompensated patients. Methods: Analysis of 615 non‐SBP infections (161 urinary infections (UTI), 95 cellulitis, 92 suspected infections, 92 bacteraemias, 84 pneumonias, 21 bronchitis, 18 cholangitis, 15 spontaneous empyema, 13 secondary peritonitis, 24 other). Results: Ninety‐six percent of infections solved. AKI and type‐1 HRS were developed in 37% and 9% of infections respectively. Overall hospital, 30‐day and 90‐day mortality rates were 11%, 12% and 18% respectively. Clinical course and mortality differed markedly across infections. Endocarditis, osteoarticular infections, pneumonia, spontaneous bacteraemia, cholangitis, secondary peritonitis and UTI showed higher rates of AKI. Prevalence of type‐1 HRS was not significantly different among infections. Endocarditis, secondary peritonitis, pneumonia and bacteraemia showed lower rates of renal impairment resolution and higher hospital mortality associated with AKI (42% vs 12%, P <.0001) or type‐1 HRS (71% vs 27%, P =.003) than the rest of infections. Age (HR: 1.04), serum sodium (HR: 0.91), serum bilirubin (HR: 1.06), INR (HR: 1.91), hepatic encephalopathy (HR: 2.44), ascites (HR: 3.06) and multidrug‐resistant isolation (HR: 2.27) at infection diagnosis were independent predictors of death during hospitalization. Conclusions: Non‐SBP infections constitute a heterogeneous group regarding clinical course and prognosis. Endocarditis, secondary peritonitis, pneumonia and bacteraemia show worse prognosis. The combination of data of liver and renal dysfunction and of the type of infection allows the identification of patients with poor prognosis.